2021
DOI: 10.1007/s10803-021-05221-3
|View full text |Cite
|
Sign up to set email alerts
|

Camouflaging Intent, First Impressions, and Age of ASC Diagnosis in Autistic Men and Women

Abstract: Camouflaging of autistic traits may make autism harder to diagnose. The current study evaluated the relations between camouflaging intent, first impressions, and age of autism diagnosis. Participants comprised autistic and non-autistic adults (n = 80, 50% female) who completed the Camouflaging of Autistic Traits Questionnaire. They were later video-recorded having a conversation with a person unaware of their diagnostic status. Ten-second clips from half these videos were later shown to 127 non-autistic peers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
0
13
0
1
Order By: Relevance
“…No significant correlation between IQ and camouflage was found by Lai et al ( 35 ); However, the authors found a positive correlation between camouflage and signal detection sensitivity. Similarly, Belcher et al reported no correlation between camouflage and executive function or theory of mind in 80 autistic participants ( 28 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…No significant correlation between IQ and camouflage was found by Lai et al ( 35 ); However, the authors found a positive correlation between camouflage and signal detection sensitivity. Similarly, Belcher et al reported no correlation between camouflage and executive function or theory of mind in 80 autistic participants ( 28 ).…”
Section: Resultsmentioning
confidence: 97%
“…It has been revealed by three studies that camouflage behavior is more common in autistic females rather than males ( 30 , 33 , 35 ). However, some studies could not find the gender difference in the non-autistic population ( 26 , 28 , 30 ) or in samples of autistic adults ( 27 , 28 ). Using a Compensation Checklist, Livingston et al did not find a relationship between compensation score and sex ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, by characterizing all instances of camouflaging as a form of passing, we risk adopting too narrow of a focus on the phenomenon and unduly limiting our conceptions of what camouflaging looks like as a consequence. It is possible to object that the cases of people whose behavior does not prima facie fall under the notion of passing, are nonetheless cases of people trying to pass as neurotypicals without succeeding (see also Belcher et al, 2022). While this might be the case, we have to be cautious about attributing such intention to people whose goals appear to be narrower, such as being able to enjoy more circumscribed social situations.…”
Section: Camouflaging As Passingmentioning
confidence: 99%
“…Zgodnie z szacunkami Centers for Disease Control and Prevention (2021) w Stanach Zjednoczonych kryteria diagnostyczne ASD może spełniać nawet 1 na 44 dzieci, przy średnim wieku rozpoznania wynoszącym nieco ponad 4 lata (Centers for Disease Control and Prevention, 2021). Wielu klinicystów i badaczy różnic międzypłciowych w autyzmie wskazuje dodatkowo, że dziewczęta i kobiety z ASD diagnozowane są później aniżeli chłopcy i mężczyźni (Belcher et al, 2022;Ormond et al, 2018;Rynkiewicz et al, 2016Rynkiewicz et al, , 2021. Niektóre pacjentki nie otrzymują diagnozy ASD w ogóle, a powodem jest brak odpowiednio wyszkolonych specjalistów (Lai i Baron-Cohen 2015;Rynkiewicz et al, 2019).…”
Section: Wstępunclassified